2011
DOI: 10.1136/jnnp.2010.234153
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stroke and related burden among older people living in Latin America, India and China

Abstract: ObjectivesDespite the growing importance of stroke in developing countries, little is known of stroke burden in survivors. The authors investigated the prevalence of self-reported stroke, stroke-related disability, dependence and care-giver strain in Latin America (LA), China and India.MethodsCross-sectional surveys were conducted on individuals aged 65+ (n=15 022) living in specified catchment areas. Self-reported stroke diagnosis, disability, care needs and care giver burden were assessed using a standardise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
110
4
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 32 publications
5
110
4
13
Order By: Relevance
“…Uncontrolled hypertension is a key, potentially preventable and readily treatable, risk factor for many prevalent diseases including stroke, ischaemic heart disease, renal insufficiency and dementia (Steyn et al, 2005;Ferri et al, 2011). Hypertension itself shares risks factors (such as obesity and lack of exercise) with other conditions, such as diabetes.…”
mentioning
confidence: 99%
“…Uncontrolled hypertension is a key, potentially preventable and readily treatable, risk factor for many prevalent diseases including stroke, ischaemic heart disease, renal insufficiency and dementia (Steyn et al, 2005;Ferri et al, 2011). Hypertension itself shares risks factors (such as obesity and lack of exercise) with other conditions, such as diabetes.…”
mentioning
confidence: 99%
“…The study performed by Friedrichs et al in Veranópolis city included individuals from 80 years and found prevalence of 4.9% . Study conducted by Ferri et al 22 in urban and rural regions of China, India and Latin America (Cuba, Dominican Republic, Mexico, Peru and Venezuela) assessed individuals from 65 years and found gross prevalence of stroke between 6 and 9% in urban areas of Latin America. Two other studies in South America showed lower prevalence, but in rural areas: 1.8% in Bolivia (adults from 35 years) 23 and 0.8% in Argentina (adults from 40 years) 24 .…”
mentioning
confidence: 99%
“…According to a study conducted in Latin America, the proportion of stroke survivors requiring care varies between 20% and 39%. A significant proportion of these survivors have a moderate or severe disability and require the assistance of a caregiver, increased family support and resource utilization from the health system and other social institutions 2 . In recent years, different studies have evaluated the functional prognosis through determinants prior to disease or from the acute/subacute stroke phases 3,4 .…”
mentioning
confidence: 99%
“…, Jamary Oliveira-Filho 1 , Elen Beatriz Pinto 1,2 Stroke, besides being an important cause of death, is the leading cause of severe disability and dependence, affecting activities of daily living (ADL) 1 . According to a study conducted in Latin America, the proportion of stroke survivors requiring care varies between 20% and 39%.…”
mentioning
confidence: 99%